The Resilience of Traditional Trade Union Practices in the Revitalisation of the Argentine Labour Movement - Atzeni, Maurizio (2007)
Market reforms have posed similar challenges to trade unions worldwide. In this regard, the current situation in Argentina does not differ from the global trend. De-industrialisation, de-centralisation of collective bargaining, reduction of the formal sector, flexibility in the labour market and the use of labour power have all affected trade unions’ capacity to mobilise workers and play a major progressive role in society. In addition, particularly over the last decade, the effects of thirty years of economic liberalisation combined with an explosion in the rate of unemployment has led to mass poverty and enormous class divisions, changing the landscape of social mobilisation in Argentina. On the one hand, mass unemployment disciplined wage-labourers; on the other, new territorial organisations, mainly of those workers now unemployed – the so-called piqueteros (for picket) – have proliferated and sustained the virulent social protests for employment and social programmes which characterised the country at the turn of the century. In this context, scholars have tended to assume the definitive demise of trade unions and their methods of struggle, turning their attention to the new social movements.